The effect of cognitive dissonance on customer loyalty among demarketed segments in the banking sector with communication openness as a moderator - Kigen, Fiona (University of the Witwatersrand, Johannesburg, 2024)
A critical challenge for firms is managing customers who are targeted for one product but not another. For instance, banks may need to navigate how to retain a customer who holds a bank account but is declined for a home loan, all while preserving the customer’s commitment, trust and loyalty in the institution. This action of selectively offering products to customers is referred to as demarketing, which is a situation where a seller induces a certain preferred segment of the market to complete a transaction, while discouraging certain other segments from completing the same transaction. A possible effect of the feelings of disappointment from customers who have been demarketed is cognitive dissonance, described as the feelings humans face when they have contradictory thoughts that cause conflict. This study, through cognitive dissonance theory and commitment-trust theory lenses, focused on customer loyalty as an outcome of commitment and trust, following cognitive dissonance arising from a demarketing effort. It also looked at the moderating effect of communication openness on the relationship between cognitive dissonance and satisfaction. The study tested a theoretical model merging the cognitive dissonance model and the commitment-trust theory of relationship marketing to theoretically test the relationships between cognitive dissonance and customer loyalty. This research was quantitative and utilised the experimental method, where a vignette was presented to study participants, followed by a survey utilising validated scales. The target population comprised of adults (over the age of 18) residing in South Africa who are eligible to apply for unsecured consumer credit facilities from a registered credit provider as per the National Credit Act (No. 34 of 2005). Five hundred and five responses were collected for final analysis, and Covariance-Based Structural Equation Modelling (CB-SEM) on SPSS AMOS 27 was used to test the hypotheses. The study findings indicated that being demarketed results in cognitive dissonance in customers, which further results in lower levels of satisfaction, trust, commitment and loyalty. However, dissonance reduction mechanisms that customers deploy were found to moderate this effect. Communication openness on the other hand was not found to have a moderating effect. Empirically, this research may assist firms to understand how best to minimize cognitive dissonance in their demarketing efforts, and thus limit damage to customer relationships. The findings of this study aim to contribute to knowledge in the fields of demarketing, cognitive dissonance and relationship marketing, responding to calls in literature for more research into strategies aimed at reducing cognitive dissonance. This is especially relevant in the South African context which experiences a very high level of loan declines and where consumers generally express low levels of satisfaction with their banks.
A research report submitted in fulfillment of the requirements for the PhD in Business Studies (Marketing), in the Faculty of Commerce Law and Management, School of Business Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Demarketing; Cognitive Dissonance; Satisfaction. Trust; Commitment; Loyalty; Communication Openness; SDG-8: Decent work and economic growth